To Great Slave And Great Bear : P.G. Downes's Journal Of Travels North From Ile À La Crosse In 1938 [Part II] - Cockburn, R.H. (ARCTIC, 1985)
The narrative of P.G. Downes's trip by canoe, boat, and plane from Ile à la Crosse to Great Bear and Great Slave lakes in 1938, in which he presents a detailed account of his feelings, thoughts, and experiences, as well as his observations on individual men and women, northern lore, and geographic characteristics of the region. The journal will appear as five installations in Arctic.Key words: Ile à la Crosse, Lac La Loche, Swan Lake Portage, Clearwater River, Athabaska River, Slave River, Fort Smith, Great Slave Lake, Mackenzie River, Great Bear Lake, Eldorado, Cameron Bay, Yellowknife, Chipewyans, John Hornby, George M. Douglas, Paul "King" Beaulieu Mots clés: île à la Crosse, lac La Loche, lac du Cygne, Portage, rivière à l'Eau-Claire, rivière Athabasca, rivière des Esclaves, Fort Smith, Grand Lac des Esclaves, fleuve Mackenzie, Grand Lac de l'Ours, Eldorado, baie Cameron, Yellowknife, Chipewyans, John Hornby, George M. Douglas, Paul "King" Beaulieu